Applications of Deep Eutectic Solvents Related to Health, Synthesis, and Extraction of Natural Based Chemicals - Laura Lomba; Cristina B. García; Mª Pilar Ribate; Beatriz Giner; Estefanía Zuriaga (Applied Sciences, 2021)
Deep eutectic solvents are liquid mixtures of solid components at room temperature, which present exceptional properties: high solvent capacity, high biodegradation, low volatile organic compound character, and relatively low toxicity. Furthermore, there are an important number of DES described, formed by different components and ratios, and thus, the studied applications are also numerous. In this review, we focused on the applications related to health. One of the most promising applications of DES is the development of oral liquid formulations of poorly soluble active pharmaceutical ingredients, although it currently remains at an early stage. We have analyzed the potential and limitations of DES with this regard. Furthermore, DES have been used as synthesis media. In this work, we revised the use of DES to obtain bioactive natural products via synthesis or extraction process. Finally, the usefulness of DES in other interesting applications for promoting health has been also examined: this is the case of genomics studies, nano-carriers for the encapsulation of anticancer drugs or stabilization of samples for medical purposes.